PERNIKAHAN USIA DINI DALAM PERSPEKTIF HADIS: TELAAH KONTEMPORER MELALUI PENDEKATAN PSIKOLOGI - Annisa Az Zahra; Alvia Nuristikha Putri; A. Halil Thahir; Niwari; Ibnu Hajar Ansori (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Early marriage is a significant issue in social and health studies, often having profound effects on individuals and communities. This article addresses early marriage by focusing on the interpretation of Hadith concerning the marriage of the Prophet Muhammad (SAW) to Aisha (RA) and its relevance in a modern context. Employing a qualitative approach and literature review methodology, the study gathers data from Hadith exploration and literature analysis to provide contextual and applicative understanding. The findings underscore the importance of aligning Hadith interpretations with contemporary social conditions and the need for effective strategies to address the psychological, reproductive health, and social impacts of early marriage. Despite the historical Islamic context of early marriage having different foundations, its psychological, reproductive health, and social implications require in-depth consideration. Psychologically, early marriage often leads to stress and emotional disturbances due to adolescent mental immaturity. Reproductively, risks of complications rise due to physical and hormonal immaturity, including bleeding, miscarriage, or other health issues. Socially, the potential for high divorce rates and family instability may disrupt social and emotional well-being. The study concludes that adapting Hadith interpretations to current social contexts and implementing effective approaches to address early marriage issues is essential.